Clima escolar e preconceito contra diversidade sexual e de gênero em escolas - Lindern, Daniele (2020)
Prejudice is defined as a hostile attitude, directed at individuals because they belong to a certain group, and which creates or sustains a hierarchical relationship between people. Since it refers to categories of people and not to isolated individuals, prejudice is socially shared. The relationships between the groups that perpetuate prejudice and the groups that are victimized are associated with the existence and perpetuation of that prejudice. Therefore it can be understood that many factors that cause this phenomenon come from social situations, such as interactions within peer groups. Peer groups are defined as groups of people of equal hierarchy and who share common interests and/or characteristics, such as age, frequenting the same club or being classmates at school. School is the foremost place for development and establishment of peer relations. As an important environment of development, school can be characterized not only as a space for healthy cognitive and social development, but also as a stage for social segregation and hierarchy, through prejudice. There are different types of prejudice. Studies have investigated the impact of prejudice against sexual and gender diversity in the culture and climate of schools, but in the Brazilian context the investigation of these themes is still little explored. Prejudice against sexual and gender diversity at school tends to affect peer relations over time, which can result in a negative school climate and culture. School climate characterizes the quality of life at school according to the experiences of people at a school, while school culture refers to the norms and beliefs that define the institutional identity of the school. The specific objectives of this thesis were: to identify the prevalence of prejudice (individual and perceived in peer groups) against sexual and gender diversity in schools and the perception of school climate; to investigate whether there would be differences between the groups of participants (LGBT students - lesbian, gay, bisexual and transgender - and nonLGBT students) with respect to prejudice and school climate; to investigate if there would be relationships between prejudice, school climate and the other study variables; to investigate if the prejudice perceived in peers would be a moderating variable between the feeling of belonging to the school and the school climate and understand how students and non-LGBT teachers perceive the impact of prejudice in their relationship patterns at school. The research was divided into two sequential studies. Study I had a cross-sectional quantitative design. The instruments used were a Sociodemographic Data Questionnaire, the Scale of Prejudice Against Sexual Diversity and Gender and the Delaware School Climate Survey (DSCS-S) - Brazilian version for students. 538 students from three public schools in the city of Porto Alegre participated in the study, named “School A” (n = 87), “School B” (n = 111) and “School C” (n = 330). Of the total number of students, 51.5% declared to be female (n = 277) and 16.5% (n = 89) identified themselves as LGBT. The mean age was 16.02 years (SD = 1.63). Differences between groups were identified, with both the LGBT group and the female students reporting a worse perception of school climate, less sense of belonging to their school and less individual prejudice against sexual and gender diversity. Students who claimed to have LGBT people in their lives reported less individual prejudice compared to those who had no close contact with these minorities. Broadly, the results of the other analyses suggest that prejudice perceived in the peer groups predicts a worse perception of school climate, and that when accepted and valued among peers, the prejudice can be positively associated with the school climate. Still prejudice perceived in peers, at higher levels, tends to strengthen the association between belonging and the school climate. Study II had a cross-sectional qualitative design. Eight participants from Study I were randomly selected, four teachers and four students. The participants responded to a semi-structured interview, and the transcripts were analysed using the content analysis method (Bardin, 2016). During data collection, the schools went on strike, and due to this occurrence, seven interviews were conducted, totalling four teachers (women) and three students (two boys and one girl). The results revealed that the participants perceive that prejudice against sexual and gender diversity is present in their schools, especially indirectly, through jokes and pejorative language. Thus, the findings of studies I and II suggest that prejudice against sexual minorities negatively impacts the school environment, which may lead to school climates and cultures that support and reinforce heteronormativity in schools.